Image Digitization of Colorimetric Detection of Acephate Based on Its Complexation with Citrate-Capped Gold Nanoparticles - Mohd Junaedy Osman; Wan Md Zin Wan Yunus; Keat Khim Ong; Buong Woei Chieng; Noor Azilah Mohd Kassim; Siti Aminah Mohd Noor; Victor Feizal Knight; Jahwarhar Izuan Abd Rashid; Chin Chuang Teoh (Journal of Chemistry)
Acephate (Ac), an organophosphate (OP) insecticide, is very harmful to human and the environment. Conventional techniques of detection are sensitive and selective but relatively time-consuming, expensive, and require trained personnel. This paper describes the use of an image processing technique to digitize the red values (RVs) of the colour image of Ac-capped gold nanoparticles (Ac-Cit-AuNPs) complex captured using a digital microscope to improve the detection accuracy and precision. The formation of the suspension was characterised using laser test, ultraviolet-visible spectrophotometer (UV-Vis), high-resolution transmission electron microscope (HRTEM), and Fourier Transform infrared spectroscope (FTIR). The linear regression analysis revealed that the detection sensitivity improved as the smaller gold nanoparticles were used. For quantitative measurement using image processing, a good linear relationship (R2 = 0.9905 and 0.9924) for Cit-HAuNPs and Cit-MAuNPs, respectively, between the concentration of Ac and average red values was obtained in the range of 0–8 mM. The limit of detection (LOD) for Ac was found to be 0.3 mM and 0.4 mM for Cit-MAuNPs and Cit-HAuNPs, respectively.